ToxNav germline genetic testing and PROMinet digital mobile application toxicity monitoring: Results of a prospective single-center clinical utility study-PRECISE study. - Lee, L; Starkey, T; Sivakumar, S; Fotheringham, S; Mozolowski, G; Shearwood, V; Palles, C; Camilleri, P; Church, D; Kerr, R; Kerr, D (Wiley, 2019)
INTRODUCTION: In this study (PRECISE), we assess the clinical utility of a germline DNA sequencing-based test (ToxNav) for mutations in DPYD and ENOSF1 genes to alter clinician-prescribed fluoropyrimidine doses and the use of a digital application (PROMinet) to record patient-reported chemotherapy toxicity. MATERIALS AND METHODS: Adult patients with a histological diagnosis of colorectal cancer (CRC) who consented to fluoropyrimidine-based chemotherapy were recruited prospectively and given a digital application to monitor and record associated toxicities. Patient samples were analyzed for 18 germline coding variants in DPYD and 1 ENOSF1 variant. RESULTS: Genetic testing was performed for 60 patients and identified one patient at increased risk of fluoropyrimidine-based toxicities. Uptake of genetic testing was high and results were available on average 17 days from initial clinical encounter. Patient-reported chemotherapy toxicity identified differences in 5-fluorouracil vs capecitabine regime profiles and identified profiles associated with subsequent need for chemotherapy dose reduction and hospital admission. DISCUSSION: The PRECISE clinical trial demonstrated that a germline DNA sequencing-based test can provide clinically relevant information to alter clinicians' fluoropyrimidine prescription. The study also obtained high volume, high granularity patient-reported toxicity data that might allow the improvement and personalization of chemotherapy management.